Multi-Frequency Solar Rectenna Design for Hybrid Radio Frequency–Solar Energy Harvester - Xue Luo; Ping Lu; Ce Wang; Kama Huang (Energies)
This paper put forward a hybrid energy harvester for collecting RF and solar energy in quad-band (GSM-900/1800, ISM-2400 and WiMAX-3500). By introducing diverse parasitic structures, good impedance matching with unidirectional radiation is achieved in the multi-band. Below the solar antenna, a low-power rectifier circuit is employed to achieve broadband rectification. Under the input power of 0 dBm, and maximum RF-DC conversion efficiency of 56.94% is realized. Accordingly, the hybrid energy harvester collects RF and solar energy individually or simultaneously, and then converts it into DC for power supply. With a light intensity of 1500 lux, the solar cell obtains 1.732 mW, and the rectenna can harvest additional 0.37–0.405 mW power. The proposed RF–Solar energy harvester has the advantages of multi-frequency operation, high gain, and high energy harvesting conversion efficiency.